Factors influencing consumer satisfaction for "kelulut" honey in syamille agro farm & resort - Zaini, Muhammad Helmi (2016)
Syamille Agrofarm & Resort is a famous for its honey breeding from stingless bees. However, the consumer of “Kelulut” honey based product are not satisfied with the products in Syamille Agrofarm & Resort. The owner of the resort would like take action to overcome this problem. This study was conducted to determine the factors that influence consumer satisfaction for “Kelulut” Honey. Purposive sampling was used in this study by distributed the questionnaire to visitors in Syamille Agrofarm & Resort for data collection. Descriptive Analysis, Factor Analysis and Multiple Regression Analysis were used in this study to analyze the data. The significant variables found were extracted and regrouped according to the appropriate factors in generating the new scale. Then the variable factors is analyze to get the most significant variable factors which using factor analysis. As a result, 5 factors were identified to have significant contribution in determining consumer satisfaction of “Kelulut” honey which the data was run using Multiple Regression Analysis. This finding can be used in determining consumer satisfaction.